Do Local Government Units in the Philippines Procure Medicines According to a Set Benchmark Price?. Issue 1 (29th February 2020) - Cheng, Kent Jason; Rivera, Adovich; General, Jojana Christine; Asence‐Mamporte, Amelyn; Ulitin, Allan; Miguel, Red Thaddeus; Guerrero, Anna Melissa; Florentino‐Fariñas, Irene; Sison, Karina; Lam, Hilton
Abstract : This retrospective study aimed to assess whether Philippine local government units (LGUs) procure drugs within official benchmark prices set by the Department of Health (DOH) called the Drug Price Reference Index (DPRI). Drug procurement price data found in the purchase orders or obligation requests of 35 purposively selected LGUs and LGU‐owned and ‐operated hospitals were collected. A Laspeyres index was used to measure the percent difference of the total drug expenditure when the quantities procured were priced at DPRI prices instead of supplier prices. Indices higher (lower) than 1 would indicate that drugs bought were more expensive (cheaper) than the DPRI prices. Results show that out of the 10 study sites, 8 were found to be deviant from the DPRI and indices ranged from 0.35 to 212.70, which implies that majority of LGUs are not compliant with the benchmark. The DOH already has a policy that enforces the adherence of DPRI among LGUs in place, but the policy has yet to be properly implemented. Monitoring may be done through computing the Laspeyres index described in this study. Monitoring can be delegated to DOH Regional offices to de‐load the DOH Central Office .